2006
DOI: 10.1186/ar2017
|View full text |Cite
|
Sign up to set email alerts
|

Independent associations of anti-cyclic citrullinated peptide antibodies and rheumatoid factor with radiographic severity of rheumatoid arthritis

Abstract: Several recent publications have established a strong association between anti-cyclic citrullinated peptide antibody (anti-CCP)-positive rheumatoid arthritis (RA) and carriage of shared epitope (SE) alleles. Although anti-CCP have also been associated with more severe RA, the issue of whether this is independent of rheumatoid factor (RF) has not been addressed. To identify associations between RF, anti-CCP, SE status and radiological damage, we studied a large cross-sectional cohort with longstanding RA. Indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(24 citation statements)
references
References 14 publications
0
22
2
Order By: Relevance
“…The overlap between RF and anti-CCP positivity may be greater in established RA (93% in a study of 784 RA patients, mean disease duration 18 years) [30], than in early arthritis (50 to 80% in different studies) [5,7,31]. In the present study only 58% (37/64) of antibody positive patients with persistent arthritis were positive for both RF and anti-CCP.…”
Section: Discussioncontrasting
confidence: 45%
“…The overlap between RF and anti-CCP positivity may be greater in established RA (93% in a study of 784 RA patients, mean disease duration 18 years) [30], than in early arthritis (50 to 80% in different studies) [5,7,31]. In the present study only 58% (37/64) of antibody positive patients with persistent arthritis were positive for both RF and anti-CCP.…”
Section: Discussioncontrasting
confidence: 45%
“…Another limitation is the lack of data on anti-citrullinated antibody (ACPA) status after diagnosis, which is due to the fact that for the majority of patients the diagnosis was before routine ACPA analysis was available. However, we did have data on RF, and RF positivity and ACPA positivity are known to have a major overlap in patients with RA [ 47 ]. Previous studies have indicated that predictors differ for RF/ACPA-positive versus RF/ACPA-negative RA [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variance of radiological hand and foot damage that could be explained by these measurements was 44% at 5 years and only 32% at 10 years 16. In established disease the presence of RFs and anti-citrullinated protein antigens (ACPA) are both independently associated with increased radiological damage,17 but the variance in radiological damage related to these markers is modest at 3% and 2%, respectively 17. These results highlight the need to identify additional biomarkers predictive of severe RA that could be used to target treatments more effectively.…”
Section: Introductionmentioning
confidence: 99%